Współczesne studia doktoranckie i współcześni doktoranci. Doniesienia ze zwiadu badawczego - Banaszak, Sławomir; Andrys , Magdalena; Dolata, Dorota; Iwanicka, Beata; Schmidt, Anna; Ulaniecka, Natalia (Studia Edukacyjne, 2017)
The article presents the results of a research study on the situation of contemporary post-graduate students. Focus group interviews helped obtain post-graduate students’ opinions about the conditions of starting and continuing doctoral studies. The discussion focused on three main topics: motivation to start doctoral studies, the quality and conditions of doctoral studies evaluation, and the advantages and disadvantages of undertaking doctoral studies. Analysis of the respondents’ statements shows that the motivations for starting doctoral studies vary strongly. Common in the experience of the interlocutors is a lack of stability in life (including financialstability), insecurity of employment, overload, and stress. However, post-graduate students presented also positive aspects of doctoral studies, e.g.: social prestige or the possibility of development. The last part of the article describes issues related to problems and pathological phenomena (such as ‘punctasis’/‘points, credits collecting’), pointing to systemic and individual limitations affecting the situation of doctoral students in the Polish tertiary education system.